1996
DOI: 10.1111/j.1550-7408.1996.tb02468.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Microsporidian Polar Tube Protein Reactive Monoclonal Antibody

Abstract: The microsporidia are characterized by spores containing a single polar tube that coils around the sporoplasm. When triggered by appropriate stimuli, the polar tube rapidly discharges out of the spore forming a hollow tube. The sporoplasm passes out of the spore through this tube serving as a unique vehicle of infection. Due to the unusual functional and solubility properties of the polar tube, the proteins comprising it are likely to be members of a protein family with a highly conserved amino acid compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
59
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 18 publications
(14 reference statements)
1
59
0
Order By: Relevance
“…It has also been observed that the portion of the tube already everted remains unchanged while the tube elongates and even changes direction at the tip (Weidner, 1982;Frixione et al, 1992). It should be noted that spores can be broken by mechanical pressure or by glass bead disruption, thus releasing polar tubes from the sides of the spores (Kudo, 1921;Keohane et al, 1994Keohane et al, , 1996a. It has been reported that polar tubes had a similar ultrastructural appearance regardless of whether they were triggered to activate and evert from the apical pole, or if they passively burst through the lateral walls of the spores (Weidner, 1982).…”
Section: Structure Of the Microsporidian Spore And Polar Tubementioning
confidence: 99%
See 2 more Smart Citations
“…It has also been observed that the portion of the tube already everted remains unchanged while the tube elongates and even changes direction at the tip (Weidner, 1982;Frixione et al, 1992). It should be noted that spores can be broken by mechanical pressure or by glass bead disruption, thus releasing polar tubes from the sides of the spores (Kudo, 1921;Keohane et al, 1994Keohane et al, , 1996a. It has been reported that polar tubes had a similar ultrastructural appearance regardless of whether they were triggered to activate and evert from the apical pole, or if they passively burst through the lateral walls of the spores (Weidner, 1982).…”
Section: Structure Of the Microsporidian Spore And Polar Tubementioning
confidence: 99%
“…Techniques have been described that permit the purification of spore coat proteins as well as polar tube proteins (Keohane et al, 1994(Keohane et al, , 1996a(Keohane et al, , 1999. With the publication of the genome of E. cuniculi this has permitted investigators to initial proteomic studies of the composition of this structure (Texier et al, 2003;Weiss L.M., unpublished data).…”
Section: The Microsporidian Spore Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no reaction of either antibody with lysates from insect tissues (Culex restuans, Helicovera zea, Lymentra dispar, or Acheta domesticus) under reducing or non-reducing conditions. These mAbs were further characterized using immunogold electron microscopy employing protocols previously described (Keohane et al, 1996). Both mAbs demonstrated a generalized localization to antigens in the spores of N. locustae and cross-reacted with antigens in E. cuniculi and a Pleistophora sp.…”
mentioning
confidence: 99%
“…Fusion of mouse spleen cells with myeloma cells was performed 12 weeks postimmunization using standard techniques. Supernatants from hybridomas were screened by immunoblotting using N. locustae spore lysate as the antigen as previously described (Keohane et al, 1996). Two monoclonal antibodies [mAbs] were identified that reacted with N. locustae spore lysate by immunoblotting: 3B1.23, an IgM mAb that recognized a 40-kDa antigen, and 19 F9.24, an IgG 3 mAb that recognized a group of three antigens of 12-18 kDa ( Fig.…”
mentioning
confidence: 99%